Research and implementation of fuzzing testing based on HTTP proxy - Xin SUN; Yi-yang YAO; Xin-dai LU; Xue-jiao LIU; Yong-han WU (网络与信息安全学报)
Most of the security testing tools lack of optimization of testing,configured strategy and intelligent analysis of testing results.These problems lead to the status that these tools can’t be used in Web application testing well.A fuzzing testing method towards Web application security based on HTTP proxy was proposed.The high-performance communication between HTTP proxy server and browser through the mechanism of asynchronous monitoring was realized.Configured strategy of testing cases based on pseudo code could help to do flexible and automatic tests.By using multi-dimensional ways to parse the packet,intelligent analysis of testing results was achieved.Experiments show that the tool supports mainstream Web application vulnerabilities detection and configured strategy of testing.It can detect the vulnerabilities such as directory traversal,SQL injection,cross-site scripting.